DEVELOPING A GUIDEBOOK OF BRIDGE POSITIONS FOR GRADE IV-VI STUDENTS’ SPORTS EDUCATION - Ikari, Steven David (International Journal Labs, 2022)
Background: The bridge position is contained in the material book in school and joined by other materials such as large balls, small balls, and so on, which is the advantage of this rich guidebook is that it can be used anywhere and has barcodes to access bridge position training tutorial videos. With this guidebook, learners can do bridge position activities independently and also teachers have additional material resources to train bridge position on learners. Aim: This research aims to give more insight into the development of guidebooks for sports and health education for students, especially those who are in the 4th-6th grade of elementary school. Method: The research method used in this research is Research and Development (R&D). The product developed by the researchers is a guidebook with the title